PEMANGKUR - JUICE THERAPY : REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS IN SOYA COMMUNITY HEALTH CENTER AMBON - Abdul Thalib Hamzah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction : Hypertension is a common problem in the community so that many people are addicted to medical drugs which will certainly have a bad impact on their body. Efforts are being made to shift the habit of consuming medical drugs towards complementary medicine, one of which is with pemangkur-juice. Method: The research used was a pre-experimental design with one group pretest-posttest design.The sample of this study was selected using a non-probability sampling technique with a purposive sampling (n =35, ? =0,005). Results: There is an effect of pemangkur-juice to reduction of blood pressure in hypertensive patients in Soya Public Health Center (? = 0,000) with decrease in mean (Systolic: Pre=150,29 and Post= 134,29; Dyastolic; Pre=100,29 and Post 89,43) and standard deviation (Systolic: Pre=16,713 and Post= 13,993; Dyastolic; Pre=12,945 and Post= 8,832). Conclusion: Pemangkur-Juice can be as one of complementary therapy for reducing blood pressure in patient hypertension.